Motivasi Pemberdayaan Wanita Di Kampung Tematik Lubuk Buaya Kota Padang - Sari, Novi Maya; Devita, Hendri; Faisal, Afrah Diba (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2024)
Coverage of family planning participants in the Lubuk Buaya Community Health Center working area which consists of four sub-districts, namely Parupuk Tabing, Lubuk Buaya, Pasie Nan Tigo and Ganting is 12.9%. Meanwhile, coverage of new family planning participants was 50.4%. Meanwhile, the lowest achievement rate for family planning participants was found in the Pasie Nan Tigo sub-district. Apart from that, it can be seen from the socio-economic status of the people in the Pasie Nan Tigo sub-district which is on the coast. Objective: This community service is to provide education about the importance of family planning, so that reproductive mothers or women of childbearing age will be more concerned about their reproductive health. The results of the program were implemented smoothly, and the enthusiasm of the participants (mothers and cadres) was high. This can provide support for government programs in efforts to increase mothers' awareness and knowledge about the importance of family planning. Evaluation of the lack of awareness of couples of childbearing age regarding family planning is caused by the mother's lack of knowledge. Conclusion: Through this socialization, mothers and cadres can gain useful knowledge about the importance of family planning